Collaboration in social work practice - Weinstein, Jenny, 1947-; Whittington, Colin; Leiba, Tony (Jessica Kingsley, 2003)
New or experienced social workers who are developing their collaborative practice with service users and carers and with other professionals, will find this book to be an essential source of knowledge, skills and issues for reflection. The authors explain how practitioners in social care, health and related sectors can work more effectively together in line with current developments in policy and practice, offering a critical appraisal both of the benefits and the challenges. The authors explore definitions of collaborative work, describe policy and research and give examples from their experi.